2022
DOI: 10.1002/hsr2.846
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening rural surgery in the Philippines: Essential in achieving universal health care

Abstract: The Lancet Commission on Global Surgery (LCoGS) launched Global Surgery 2030 to address the surgical services inequities with a bias toward low‐income and middle‐income countries like the Philippines. The same inequity is observed particularly when it comes to the urban‐rural divide. With more than half of the population living in rural areas, access to surgery becomes a major challenge that further impedes the much‐needed health of an economically productive workforce. The Universal Health Care [UHC] Act (RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Consisting of about 7000 islands, the Philippines is situated in the tropical region of Southeast Asia. As of 2020, it had a population of 109 million people which makes delivery of healthcare services difficult 15 16. Alkire et al had previously reported that in Southeast Asia, where the country is situated, 91.1% of the population does not have access to timely, safe and affordable surgery 17.…”
Section: Introductionmentioning
confidence: 99%
“…Consisting of about 7000 islands, the Philippines is situated in the tropical region of Southeast Asia. As of 2020, it had a population of 109 million people which makes delivery of healthcare services difficult 15 16. Alkire et al had previously reported that in Southeast Asia, where the country is situated, 91.1% of the population does not have access to timely, safe and affordable surgery 17.…”
Section: Introductionmentioning
confidence: 99%